Cognitive flexibility mediates the impact of emotion regulation strategies on negative emotions in preschool teachers - Gu, Changwei; Guo, Mengxin; Cui, Yeying; Yu, Feifei; Chen, Ya; Chu, Juanjuan; Zhou, Shuang (Frontiers in Psychology, 2025)
This study aimed to examine how cognitive flexibility mediates the associations between emotion regulation strategies and negative emotions among preschool teachers in China. A total of 392 in-service preschool teachers in Beijing were recruited through random sampling. Participants completed validated questionnaires assessing cognitive reappraisal and expressive suppression (Emotion Regulation Questionnaire), anxiety and depression (SAS and SDS), and cognitive flexibility (Cognitive Flexibility Inventory). Structural equation modeling (SEM) and bootstrapping were used to test mediation models. The results revealed that cognitive reappraisal positively predicted cognitive flexibility, which in turn was associated with lower levels of both anxiety and depression. Conversely, expressive suppression negatively predicted cognitive flexibility, which indirectly contributed to increased negative emotions. However, the direct effects of expressive suppression on anxiety and depression were not statistically significant. These findings suggest that cognitive flexibility serves as a crucial psychological mechanism through which emotion regulation strategies impact mental health. This study advances current theoretical models by highlighting cognitive flexibility as a mediating factor in preschool teachers’ emotional experiences.